Assessment of Knowledge, Attitude, and Practice of Physicians toward Pharmacovigilance in Public and Private Hospitals in Jordan - Banat, Hayaa; Alsbou, Mohammed; Bawaresh, Nidaa; El-Dahiyat, Faris; Jaber, Jaber; Tawalbeh, Khalid; Ahmad, Dana; Batarseh , Adel (Jordan Medical Journal, 2022)
Knowledge, attitude, and practice toward pharmacovigilance (PV) among healthcare providers are strongly associated with reporting of adverse drug reactions (ADRs). This study was conducted to evaluate knowledge, attitude, and practice toward pharmacovigilance and to identify barriers for ADR reporting among physicians working at public and private hospitals in Jordan. This study was conducted using an online questionnaire in the Arabic language, designed by the members of the Health Hazard Evaluation Committee of the Jordan Food and Drug Administration (JFDA) between (August 2016 to December 2017). The questionnaire was completed using Google Forms online. A total of 341 physicians completed the questionnaire online. The rate of reporting of ADRs is low among physicians, only 4.7% have reported an ADR. The majority of physicians had never heard the term PV before. Respondents also lacked awareness of the existence of a PV centre in Jordan, and were unaware that monitoring of ADRs is carried out by the JFDA. Although the majority of physicians had never seen the ADR form, many had positive attitudes toward reporting ADRs. According to participant responses, the main barriers to reporting are: 1) not knowing how to report, 2) not knowing the importance of reporting, 3) unavailability of the ADR form, and 4) general time pressure in the work environment. Although there is a low rate of ADR reporting among physicians, doctors have a positive attitude toward PV and are willing to implement ADR reporting in their practices. More education and training sessions are needed in order to raise physician awareness and knowledge of PV, and to enhance ADR reporting.